Pregunta
upstudy study bank question image url

6 Let \( f \) be the function defined by \( f(x)=\frac{a x+b}{c x+d} \) and its representative curve. Calculate the real numbers \( a, b, c \) and \( d \) so that (H) passes through the points \( A(4 ; 1) \) and \( B(-2 ; 4) \) and admits the line of equation \( y=3 \) as asymptote.

Ask by Kirk Hilton. in Lebanon
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( a = 3 \), \( b = -10 \), \( c = 1 \), \( d = -2 \).

Solución

To determine the real numbers \( a, b, c, \) and \( d \) for the function \( f(x) = \frac{a x + b}{c x + d} \) that satisfies the given conditions, let's analyze each condition step by step. ### 1. Horizontal Asymptote \( y = 3 \) For the rational function \( f(x) = \frac{a x + b}{c x + d} \), the horizontal asymptote is determined by the leading coefficients of the numerator and the denominator. Specifically: \[ \text{As } x \to \pm\infty, \ f(x) \approx \frac{a}{c} \] Given that the horizontal asymptote is \( y = 3 \), we have: \[ \frac{a}{c} = 3 \quad \Rightarrow \quad a = 3c \] ### 2. Passing Through Point \( A(4, 1) \) Substituting \( x = 4 \) and \( f(4) = 1 \) into the function: \[ \frac{a \cdot 4 + b}{c \cdot 4 + d} = 1 \quad \Rightarrow \quad 4a + b = 4c + d \] Using \( a = 3c \): \[ 4(3c) + b = 4c + d \quad \Rightarrow \quad 12c + b = 4c + d \quad \Rightarrow \quad b = -8c + d \quad \text{(Equation 1)} \] ### 3. Passing Through Point \( B(-2, 4) \) Substituting \( x = -2 \) and \( f(-2) = 4 \) into the function: \[ \frac{a \cdot (-2) + b}{c \cdot (-2) + d} = 4 \quad \Rightarrow \quad -2a + b = -8c + 4d \] Using \( a = 3c \): \[ -2(3c) + b = -8c + 4d \quad \Rightarrow \quad -6c + b = -8c + 4d \quad \Rightarrow \quad b = -2c + 4d \quad \text{(Equation 2)} \] ### 4. Solving the System of Equations From **Equation 1** and **Equation 2**: \[ -8c + d = -2c + 4d \quad \Rightarrow \quad -6c = 3d \quad \Rightarrow \quad d = -2c \] Substituting \( d = -2c \) back into **Equation 1**: \[ b = -8c + (-2c) = -10c \] ### 5. Final Values We now have: \[ a = 3c, \quad b = -10c, \quad d = -2c \] To express the solution in specific terms, we can choose \( c = 1 \) (since \( c \) is a free parameter): \[ a = 3, \quad b = -10, \quad c = 1, \quad d = -2 \] ### **Final Answer:** One such solution is a = 3, b = –10, c = 1, and d = –2. Thus,  a = 3,  b = −10,  c = 1,  d = −2.

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Mind Expander

To find the values of \( a, b, c, \) and \( d \), we know that the function \( f(x) = \frac{ax + b}{cx + d} \) needs to satisfy the following conditions: 1. The function passes through the points \( A(4, 1) \) and \( B(-2, 4) \). 2. The horizontal asymptote is \( y = 3 \). From the asymptote condition, we know that as \( x \to \infty \), \( f(x) \approx \frac{a}{c} \). For this to equal 3, we have the equation: \[ \frac{a}{c} = 3 \quad \Rightarrow \quad a = 3c. \] Now we'll substitute this relationship into the equations derived from the points A and B. **Using Point A (4, 1):** \[ f(4) = \frac{3c(4) + b}{c(4) + d} = 1, \] which leads to: \[ 12c + b = 4c + d. \] Rearranging gives us: \[ 8c + b - d = 0 \quad \text{(1)}. \] **Using Point B (-2, 4):** \[ f(-2) = \frac{3c(-2) + b}{c(-2) + d} = 4, \] so we have: \[ -6c + b = -2c + d. \] Rearranging gives us: \[ -4c + b - d = 0 \quad \text{(2)}. \] Now we can solve the system of equations formed by (1) and (2): From (1): \[ b = d - 8c, \] Substituting into (2): \[ -4c + (d - 8c) - d = 0, \] which simplifies to: \[ -4c - 8c = 0 \quad \Rightarrow \quad -12c = 0. \] This implies \( c = 0 \), which isn’t viable since it would make \( f(x) \) undefined. Next, let's directly encode \( b \) and \( d \) in terms of \( c \) from the asymptote condition. From the above solutions, we can express both equations in \( d \): Using (1) and solving for \( d \): \[ d = 8c + b, \] and substituting \( d \) into (2): \[ -4c + b - (8c + b) = 0 \Rightarrow -4c - 8c = 0 \implies b = 12c. \] Now with \( b = 12c \): Substituting \( b = 12c \) back into the equation for \( d \): \[ d = 8c + 12c = 20c. \] So we have \( a = 3c, b = 12c, d = 20c \). Now we just need arbitrary values for \( c \) to find specific values. If we choose \( c = 1 \): - \( a = 3(1) = 3 \) - \( b = 12(1) = 12 \) - \( d = 20(1) = 20 \) Thus, our coefficients are: \[ a = 3, \quad b = 12, \quad c = 1, \quad d = 20. \] The final function is: \[ f(x) = \frac{3x + 12}{x + 20}. \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad